DOT1L inhibition attenuates graft-versus-host disease by allogeneic T cells in adoptive immunotherapy models - Yuki Kagoya (Nature Portfolio, 2018)
Adoptive T cell therapy using an allogeneic T cell graft is an encouraging therapeutic approach in cancer, but issues such as graft-versus-host disease can hinder applicability. Here, the authors show that DOT1L inhibition or DUSP6 overexpression in T cells attenuates graft-versus-host disease but retains anti-tumour activity in mouse models.